Keyhole versus Sugarbaker techniques in parastomal hernia repair following ileal conduit urinary diversion: a retrospective nationwide cohort study - Mäkäräinen-Uhlbäck Elisa; Vironen Jaana; Vaarala Markku; Nordström Pia; Välikoski Anu; Kössi Jyrki; Falenius Ville; Kechagias Aristotelis; Mattila Anne; Ohtonen Pasi; Scheinin Tom; Rautio Tero (BioMed Central Ltd., 2022)
The results of parastomal hernia repair in the setting of ileal conduits are below optimal in this nationwide cohort comparing keyhole to Sugarbaker repair in elective parastomal hernia repair. Nonetheless, the Sugarbaker technique should be further studied to confirm the encouraging results of this cohort in terms of recurrence.\nPrevious research on parastomal hernia repair following ileal conduit urinary diversion is limited. This nationwide cohort study aims to present the results of keyhole and Sugarbaker techniques in parastomal hernia repair in the setting of ileal conduit urinary diversion.\nAll patients in this cohort underwent primary elective parastomal hernia repair following ileal conduit urinary diversion in four university hospitals and one central hospital in Finland in 2007-2017. Retrospective clinical data were collected from patient registries to compare keyhole and Sugarbaker parastomal hernia repair techniques. The primary outcome was parastomal hernia recurrence during the follow-up from primary surgery to the last confirmed follow-up date of the patient. The secondary outcomes were reoperations during the follow-up and complication rate at 30 days' follow-up.\nThe results of 28 hernioplasties were evaluated. The overall parastomal hernia recurrence rate was 18%, the re-operation rate was 14%, and the complication rate was 14% during the median follow-up time of 30 (21-64) months. Recurrence rates were 22% (4/18) after keyhole repair and 10% (1/10) after Sugarbaker repair. Re-operation rates referred to keyhole repair were 22% and Sugarbaker repair 0% during follow-up. The majority of reoperations were indicated by recurrence. Complication rates were 17% after keyhole and 10% after Sugarbaker repair during the 30 days' follow-up.\nCONCLUSION\nBACKGROUND\nMETHOD\nRESULTS